60 A comparison of HFrEF vs HFpEF's clinical workload and cost in the first year following hospitalisation and enrollment in a disease management program. (28th September 2016) - Murphy, T; Waterhouse, D; James, S; Casey, C; Fitzgerald, E; O'Connell, E; Watson, C; Gallagher, J; Ledwidge, M; McDonald, K
Abstract : Background: Admission with heart failure (HF) is a milestone in the progression of the disease, often resulting in higher intensity medical care and ensuing readmissions. Whilst there is evidence supporting enrolling patients in a heart failure disease management program (HF-DMP), not all reported HF-DMPs have systematically enrolled patients with HF with preserved ejection fraction (HFpEF) and there is a scarcity of literature differentiating costs based on HF-phenotype. Methods: 1292 consenting, consecutive patients admitted with a primary diagnosis of HF were enrolled in a hospital based HF-DMP and categorised as HFpEF (EF ≥ 45%) or HFrEF (EF < 45%). Hospitalizations, primary care, medications, and DMP workload with associated costs were evaluated assessing DMP clinic visits, telephonic contact, medication changes over 1 year using a mixture of casemix and micro-costing techniques. Results: The total average annual cost per patient was marginally higher in patients with HFrEF €13, 011 (12011, 14078) than HFpEF, €12206 (11009, 13518). However, emergency non-cardiovascular admission rates and average cost per patient were higher in the HFpEF vs HFrEF group (0.46 vs 0.31 per patient/12 months). In the first 3 months of the outpatient HF-DMP the HFrEF population cost more on average €791(764, 819) vs €693(660, 728). Conclusion: There are greater short-term (3 month) costs of HFrEF versus HFpEF as part of a HF-DMP following an admission. However, long-term (3–9 month) costs of HFpEF are greater because of higher non-cardiovascular rehospitalisations. As HFpEF becomes the dominant form of HF, more work is required in HF-DMPs to address non-cardiovascular rehospitalisations and to integrate hospital based HF-DMPs into primary healthcare structures.